Orang Bugis: Konstukrsi Identitas Baru Di Tanah Banten 1970-2000-an - Ahmad Subair (Universitas Negeri Makassar, 2022)
This study aims to determine the traces of the presence of the Bugis people in Banten Lama, using historical research methods, namely heuristics, criticism, interpretation, and historiography. The results of this study indicate that the background of the existence of the Bugis people in Banten started after the makassar war (17th century) which made many officials of the Gowa kingdom and their ethnic Bugis allies to go to Banten as a new place to fight the Dutch. However, during this period there was no Bugis settlement in karangantu (banten lama). Entering the 1970s, Bugis people arrived from Sumatra to karangantuk because it was caused by economic factors, namely that there was a Karangantuk port as an infrastructure that supported the life of small industries. These industries are capture fisheries, wood processing industry, shipbuilding (fishing boats). The development of the Karangantuk coast gave birth to multiple effects, such as an increase in the population of the Bugis people, causing some Bugis people to work in various sectors, such as a cottage industry for making yeast, employees in garment factories and wood factories. In the political field, some Bugis people also fill important government positions, contribute to building the province of Banten, and also contribute to the scope of regional organizations such as the association of the South Sulawesi people in Banten.